Targeting the tight-junctions of the conventional outflow pathway in primary open-angle glaucoma. - CASSIDY, PAUL SIMON (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2018)
Primary open-angle glaucoma (POAG) is one of the leading causes of blindness worldwide, affecting an estimated 44.1 million people (Tham et al. 2014). POAG is characterised by elevated intraocular pressure (IOP) due to increased resistance to the outflow of aqueous humor (AH) through the conventional outflow pathway, comprising the trabecular meshwork (TM) and Schlemm?s canal (SC), through which the majority of AH drainage occurs in humans. Elevated IOP causes damage to the axons of the optic nerve, with subsequent retinal ganglion cell (RGC) death in the retina, together termed glaucomatous optic neuropathy. As RGC transmit visual signals from the retina to the brain, this damage leads to a progressive, irreversible loss of visual field. The most common current treatments for POAG are topically applied medications that aim to reduce IOP through lowering the production rate of AH, or increasing the outflow rate of AH through the unconventional outflow pathway. There is an unmet need for therapies that target the site of increased outflow resistance in POAG, the conventional outflow pathway. A novel approach to the treatment of POAG is investigated herein through targeting of the conventional outflow pathway. AH enters SC either via a transcellular route, through large transcellular pores, or a paracellular route, through paracellular pores at tight junction (TJ) mediated cell boundaries. Potential TJ proteins were identified as therapeutic targets and the ability to downregulate these selected TJ proteins using siRNA was demonstrated. The effect of downregulation of these TJ proteins was investigated in wildtype mice through injection of siRNA into the anterior chamber, showing an increase in the outflow of AH from the anterior chamber and a reduction in IOP through increasing the number of open intercellular pores. This demonstrated the viability of this downregulation as a potential novel therapeutic approach to the treatment of POAG. IOP reduction and AH outflow increase was also demonstrated in a mouse model of steroid-induced glaucoma. The same approach was attempted in wildtype primates, with no effect on AH outflow or IOP detected, with later analysis showing that downregulation of target TJ proteins had been unsuccessful in these animals. Potential improved RNAi delivery mechanisms are discussed. In addition, the effect of the cytokine interleukin-18 (IL-18) on SC permeability and AH outflow was investigated. IL-18 is known to affect vascular permeability and TJ expression, and is upregulated in response to anti-VEGF therapy. Treating cultured human SC cells in vitro with recombinant IL-18 resulted in decreased permeability, and upregulation of the TJ protein tricellulin. In vivo injection of IL-18 caused a reduction in AH outflow facility, while measurement of outflow facility in knockout mice deficient in active IL-18 showed an increased level of AH outflow as compared to wildtype controls, indicating a potential role for IL-18 in regulation of AH outflow. Analysis of human POAG patient AH, and AH from mouse models of glaucomatous optic neuropathy, showed no increased in IL-18 concentration in AH over controls. Together these data representation an investigation of the role of TJ proteins in outflow facility resistance generation, and the potential therapeutic effect of downregulating these proteins.
APPROVED
Keywords: Glaucoma siRNA tight-junction outflow